(untitled) (LACCEI, 2024)
The objective of the present investigation is to publicize the situation of the forests with respect to the contamination of soils by hydrocarbons. The biotechnological processes applied to soil bioremediation and the feasibility of applying them in the country were investigated. Hydrocarbons are the major contaminants due to their resistance to biodegradation and their ability to bioaccumulate in the soil. In the world it is estimated that around 2,381,000 barrels of oil are spilled per year due to spills. Similarly, only in the Peruvian Amazon there have been 566 oil spills and from 1997 to 2021 87,370.82 barrels of oil have been spilled. All this has caused social conflicts and loss of species. In the case of the Bagua province, Imaza district, Inayo annex that crosses the Norperuano Pipeline, many times due to mismanagement, the pipeline has suffered ruptures and subsequent hydrocarbon leaks. The purpose of the study is to publicize in-situ bioremediation techniques, bioventing, bioaugmentation and biostimulation, and ex-situ remediation techniques such as biopiles and landfarming. As well as the phytoremediation technique. The comparative result of the techniques showed the lines of thought that led to the selection of the most appropriate technique for the Amazonian soil of study.